A Comparative Study of Muslim and Non-Muslim Perceptions of Halal Food: Examining Trust and Confidence in Malaysia. - Chong, Ye Hao; Abdullah, Nor Hazana (Research in Management of Technology and Business, 2026)
Halal food is widely consumed in Malaysia by both Muslim and non-Muslim consumers; however, recurring concerns regarding consumer trust and confidence in halal certification have raised questions about how halal-labelled products were perceived across different religious groups. This study aimed to compare the perceptions of halal food between Muslim and non-Muslim consumers in Selangor and Johor Malaysia, focusing on factors that influenced their trust and confidence in halal-labelled products. A quantitative survey method was conducted with 324 respondents using quota sampling and data were analysed using SPSS. The Mann-Whitney U test was employed to identify the comparative differences, revealing a statistically significant difference (p<0.05) between the two groups. The results showed Muslim consumers placed a stronger reliance on halal certification and religious assurance, whereas non-Muslim consumers associated halal with aspects such as food safety, hygiene and overall product quality. Consequently, these findings highlighted that bridging the perception gap requires strengthening the credibility of certification authorities and implementing inclusive communication strategies that resonate with both communities. This research suggested that future studies could further investigate how cultural or generational factors influence perceptions of halal food.